THE INFLUENCE OF FOREIGN DIRECT INVESTMENT (FDI), EXTERNAL DEBT, AND TRADE OPENNESS (TO) ON ECONOMIC GROWTH IN EMERGING MARKET COUNTRIES WITH THE COVID-19 PANDEMIC AS A DUMMY VARIABLE - Mutiara Annisa Dhiya’ulhaq; Sri Indah Nikensari; Siti Fatimah Zahra (International Journal of Multidisciplinary Research and Literature, 2023)
One global goal to achieve is decent work and economic growth. Economic growth from one period to another reflects the achievement of a country's economic development. The factors of production owned by a country are used to produce goods and services, which will then determine the country's competency in economic growth within a certain time. This study aims to determine the effect of foreign direct investment (FDI), external debt, and trade openness (TO) on economic growth in emerging market countries with the Covid-19 pandemic as a dummy variable. The analysis technique in this study uses the least squares method, or Ordinary Least Square (OLS), for the dummy variable multiple linear regression model. The results of this study indicate that foreign direct investment (FDI), external debt, trade openness, and the Covid-19 pandemic simultaneously (together) affect economic growth. Foreign direct investment (FDI) and trade openness positively affect economic growth in emerging market countries. It is shown from the regression coefficient values that are equal to 2.044 and 5.248. Meanwhile, external debt and the Covid-19 pandemic had a negative (opposite) effect on the economic growth of emerging market countries. It is shown from the results of the regression coefficients, which are -0.007 and -2.018